Exploring AI Usage in Management Consulting Leveraging AI for Potential Benefits at the Intersection of Business and Technology - Axelsson, Felix; Källvik Leufvén, Johanna (My University, 2025)
As generative AI reshapes industries, management consulting faces a transformation. This thesis explores how consulting firms can leverage AI strategically to enhance value creation both internally and externally. Through a qualitative case study of a small and relatively newly established Swedish management consulting firm, supplemented by insights from additional consulting firms and client perspectives, this study explored the changing consultant role. In doing so, the thesis also examines what competencies and capabilities will be necessary to remain competitive and relevant in the future. The findings show that AI is not replacing human consultants, rather redefining their roles. With AI as an efficiency enabler, suitable for repetitive tasks, consultants can shift their focus to more value-enhancing parts of the project. The human aspects of consulting, referred to as soft skills and including skills such as communication and trust building, are aspects that AI is not able to fill. The study introduces the Human-AI Value Matrix, a framework for mapping how firms can position themselves by balancing AI integration with the irreplaceable aspects of human insights. The study further reinforces the concept of “Hybrid Consultants”, who combines AI literacy with domain expertise and emotional intelligence. Ultimately, the thesis argues that competitive advantage in the AI era comes not from technical capabilities alone, but from consulting firm’s ability to integrate the advantages that comes with AI into a wider context. In order to truly gain value from AI, it is necessary to have someone who can translate the insights and apply them to the unique case of every client. This provides practical implications for consulting firms seeking to stay relevant and future-proof their offering.
Keywords: artificial intelligence (AI); business models; digital transformation; human value; management consulting; value creation